Tri‐mode optical biopsy probe with fluorescence endomicroscopy, Raman spectroscopy, and time‐resolved fluorescence spectroscopy. Issue 2 (21st September 2022) - Wood, Harry Alexander Charles; Ehrlich, Katjana; Yerolatsitis, Stephanos; Kufcsák, András; Quinn, Tom Michael; Fernandes, Susan; Norberg, Dominic; Jenkins, Nia Caitlin; Young, Vikki; Young, Irene; Hamilton, Katie; Seth, Sohan; et al.
Abstract: We present an endoscopic probe that combines three distinct optical fibre technologies including: A high‐resolution imaging fibre for optical endomicroscopy, a multimode fibre for time‐resolved fluorescence spectroscopy, and a hollow‐core fibre with multimode signal collection cores for Raman spectroscopy. The three fibers are all enclosed within a 1.2 mm diameter clinical grade catheter with a 1.4 mm end cap. To demonstrate the probe's flexibility we provide data acquired with it in loops of radii down to 2 cm. We then use the probe in an anatomically accurate model of adult human airways, showing that it can be navigated to any part of the distal lung using a commercial bronchoscope. Finally, we present data acquired from fresh ex vivo human lung tissue. Our experiments show that this minimally invasive probe can deliver real‐time optical biopsies from within the distal lung ‐ simultaneously acquiring co‐located high‐resolution endomicroscopy and biochemical spectra. Abstract : Design and experimental evaluation of a 1.4 mm diameter optical fibre endoscope probe enabling fluorescence endomicroscopy, time‐resolved fluorescence spectroscopy, and Raman spectroscopy. The probe's bend limit, clinical practicality, and sensitivity to human lung tissue are investigated.